2021
DOI: 10.1021/acsaem.1c00151
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement-Enhanced Water Dissociation in Bipolar Membranes with 3D Electrospun Junction and Polymeric Catalyst

Abstract: With the use of bipolar membranes (BPMs) in an expanding range of applications, there is an urgent need to understand and improve the catalytic performance of BPMs for water dissociation, as well as to increase their physical and chemical stability. In this regard, electrospinning BPMs with 2D and 3D junction structures have been suggested as a promising route to produce high-performance BPMs. In this work, we investigate the effect of entangling anion and cation exchange nanofibers at the junction of bipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Such elaborate array architecture could form AEL-CEL interlocking layer with densely dispersed micropores. By overcoming the drawbacks in previous studies for 3D interlayers (electrospinning or photoetching template) 33,34 , this approach realized MBM with highly ordered interlayer structure at sub-micro scale and conceivably offers MBM with not only abundant WD catalytic sites but also a strong combination of both layers for relieving blistering or delamination of AEL and CEL in practical applications.…”
Section: Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…Such elaborate array architecture could form AEL-CEL interlocking layer with densely dispersed micropores. By overcoming the drawbacks in previous studies for 3D interlayers (electrospinning or photoetching template) 33,34 , this approach realized MBM with highly ordered interlayer structure at sub-micro scale and conceivably offers MBM with not only abundant WD catalytic sites but also a strong combination of both layers for relieving blistering or delamination of AEL and CEL in practical applications.…”
Section: Electrodementioning
confidence: 99%
“…− can be easily transferred through the 3D framework to Co nanoarray possessing abundant catalytic sites, which can also be proved by the depth of microporous and the bulky surface area (Supplementary Figs. 33 48 , the MBM electrosynthesis system is prospective to work with ~90% efficiency at ampere-level currents.…”
Section: Continuous Ammonia Electrosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Under reverse bias, water dissociation phenomena in BPM could be achieved even without the use of interface catalysts by optimizing the thickness and functionalization degree of each membrane layer (CEL/AEL). , Chabi et al reported the synthesis of transparent BPM from highly functionalized CEL (Nafion, NR-211 of thickness 25 ± 3 μm) and AEL (poly­(benzimidazolium), PBI of thickness 55 ± 3 μm) without the use of any interface catalysts, and the water dissociation onset potential, U diss (also denoted as V diss or E onset in the literature), was ∼0.87 V. Another homogeneous BPM of Abdu et al, made by laminating commercial anion exchange membrane (AEM, FAA of thickness 140 ± 10 μm) and cation exchange membrane (CEM, FKB of thickness 90 ± 10 μm) without any interface layer showed U diss ∼ 1.1 V, and it was reduced further by the incorporation of multilayered polyelectrolyte (poly­(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/polyethylenimine (PEI)) as the interface catalyst. McDonald and Freund reported U diss = 0.9 V with homogeneous BPM prepared by laminating commercial AEM (AHA of thickness 180 ± 5 μm) and CEM (Nafion NR-211 of thickness 20 ± 5 μm) without any interface, which could be further reduced to 0.8 V through the incorporation of graphene oxide (GO) nanoparticles as the interface catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation of water molecules is understood to be the combined effect of: (i) protonation and deprotonation of water molecules through the fixed charge groups of CEL/AEL, and (ii) second Wien effect (i.e., dissociation of weak electrolyte under applied potential) 8 . The second Wien effect is found to be dominant in BPM with no interface, 9,10 where physiochemical/electrochemical properties and available charge groups (charge density) of CEL/AEL promote water dissociation 11,12 . Liu et al 13 reported drop in onset water dissociation potential (U diss ) with the extent of functionalization, that is, higher charge density.…”
Section: Introductionmentioning
confidence: 99%